Determinan Competitive Advantage Tourism Destination Pada Desa Wisata Kutuh, Kecamatan Kuta Selatan, Provinsi Bali - I Wayan Chandra Adyatma; I Putu Gede Satria Wiraharja; Desak Rurik Pradnya Paramitha Nida (PT Keberlanjutan Strategis Indonesia, 2026)
This study analyzes the influence of government roles, leadership, and destination image on the competitive advantage of Kutuh Tourism Village, Badung Regency. The research employed a quantitative approach, with data collected through questionnaires administered to key stakeholders, and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings indicate that the government role has a positive and significant effect on competitive advantage (t-statistic = 2.71; original sample = 0.800), suggesting that regulatory support, infrastructure development, and promotion enhance destination competitiveness. Destination image also shows a positive and significant effect (t-statistic = 2.22; original sample = 0.805), confirming that positive tourist perceptions strengthen competitive advantage. Conversely, leadership has no significant effect (t-statistic = 0.71), indicating the need to improve local leadership capacity. The R-Square value of 0.741 indicates that the three variables collectively explain 74.1% of the variance in competitive advantage, while the Q-Square value of 0.711 demonstrates high predictive relevance. These findings provide practical implications for destination development, emphasizing that synergy between government support and destination image enhancement is a key driver for sustainable competitiveness, with leadership remaining a strategic potential that should be optimized.